Fiscal decentralisation and green total factor productivity in China: SBM-GML and IV model approaches - Zhan, Xuegang; Li, Rita Yi Man; Liu, Xiaoyu; He, Fan; Wang, Meitao; Qin, Yuan; Xia, Jing; Liao, Wangyunyan (Frontiers in Environmental Science, 2022)
This paper uses the SBM-GML model to measure and evaluate green total factor productivity based on the panel data of 30 provinces and cities in China from 2012 to 2018. It examines the impact of different dimensions of financial decentralisation on green total factor productivity. The research results show that: (1) green total factor productivity in China is improved year by year and better in central and western regions; (2) the decentralisation of fiscal revenue and expenditure significantly weakens the increase of green total factor productivity in provincial level; (3) fiscal decentralisation inhibits green total factor productivity in central and western regions with regional heterogeneity; (4) local government competition affects the relationship between fiscal decentralisation and green total factor productivity, weakens the negative effect of fiscal decentralisation on green total factor productivity. Finally, the study aims to promote green total factor productivity and sustainable development from the perspective of financial decentralisation. This paper expands the literature and evidence of financial decentralisation on green total factor productivity and offers suggestions for governments and policymakers working toward sustainable development.